2014
DOI: 10.1007/s11606-014-2955-1
|View full text |Cite
|
Sign up to set email alerts
|

Methods and Outcomes for the Remediation of Clinical Reasoning

Abstract: INTRODUCTION:There is no widely accepted structured, evidence based strategy for the remediation of clinical reasoning skills. AIM: To assess the effectiveness of a standardized clinical reasoning remediation plan for medical learners at various stages of training. SETTING: Learners enrolled in the University of Colorado School of Medicine Remediation Program. PROGRAM DESCRIPTION: From 2006 to 2012, the learner remediation program received 151 referrals. Referrals were made by medical student clerkship directo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 33 publications
2
40
0
2
Order By: Relevance
“…Formal remediation programs are effective [4], but they are labor intensive, require a longitudinal, institutional response, and are not well suited to the real-time clerkship environment where the unexpected struggling student is one of many learners on the teacher's team [5].…”
Section: Introductionmentioning
confidence: 99%
“…Formal remediation programs are effective [4], but they are labor intensive, require a longitudinal, institutional response, and are not well suited to the real-time clerkship environment where the unexpected struggling student is one of many learners on the teacher's team [5].…”
Section: Introductionmentioning
confidence: 99%
“…When considering which category is most likely involved, it must be borne in mind that causes of under-performance are often interrelated 34. A study by Guerrasio and Aagaard,14 for instance, showed that among 53 learners followed for clinical reasoning difficulties, three-quarters had “comorbidities”, ranging from insufficient knowledge (17% of students) to mental health issues (12% of residents). In such cases, the best approach is to address difficulties one by one, beginning with the predominant difficulty for that learner or the one that interferes most with their work.…”
Section: Resultsmentioning
confidence: 99%
“…Intervention studies regarding remediation have often been limited to small single-institution endeavors, and have focused on the remediation of cognitive difficulties 9,14. Although recommendations for remediation at an institutional level have recently been published,15 the best approach for clinical teachers in the field remains to be established.…”
Section: Introductionmentioning
confidence: 99%
“…An inadequate knowledge base appears the most consistent reason for error (Norman et al 2017). A number of authors have recommended tailored teaching strategies for clinical reasoning (Rencic 2011;Guerrasio and Aagaard 2014;Posel et al 2014). Most approaches pertain to education in the clinical workplace.…”
Section: How To Teach Clinical Reasoning To Junior Students?mentioning
confidence: 99%